2004
DOI: 10.1002/hlca.200490087
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Properties of 4‐Pyridoxic Acid as a Function of pH and Solvent

Abstract: The photophysical properties and acid/base equilibria of 4-pyridoxic acid ( 3-hydroxy-5-(hydroxymethyl)-2-methylpyridine-4-carboxylic acid), the final product of the catabolism of vitamin B 6 , have been studied in aqueous solutions. The ground state of 4-pyridoxic acid exhibits the different protonated forms A ± D in the range of H 0 À 6 to pH 11.5. HMQC-and HMBC-NMR Studies allowed the pH-dependent assignment of the different C-atoms, and the evaluation of the deprotonation sequence. The 3-OH group in the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
(35 reference statements)
1
6
0
Order By: Relevance
“…The pK a values of 3.7 and 7.4 were assigned to the deprotonation of the phenol moiety in form (A) and the pyridinium nitrogen in form (C), respectively. These pK a values are of similar magnitude to those determined for the structurally related compounds pyridoxamine and 4-pyridoxic acid (37,38).…”
Section: Ph Dependence Of the Absorbance Of Qtsupporting
confidence: 77%
“…The pK a values of 3.7 and 7.4 were assigned to the deprotonation of the phenol moiety in form (A) and the pyridinium nitrogen in form (C), respectively. These pK a values are of similar magnitude to those determined for the structurally related compounds pyridoxamine and 4-pyridoxic acid (37,38).…”
Section: Ph Dependence Of the Absorbance Of Qtsupporting
confidence: 77%
“…Most of the metabolites are clearly organic anions whereas others, such as 4-pyridoxic acid, are likely to be so at physiological pH. 35 Several of these metabolites have been shown to directly interact with the Oat1 transporter by in vivo and in vitro assays. The identified known and novel compounds, from the untargeted metabolomic analysis have allowed us to design Oat1 metabolite-specific pharmacophores using computational modeling methods and predicted further compounds with the pharmacophore-directed search of the NCI database.…”
Section: Discussionmentioning
confidence: 99%
“…Pyridoxamine showed that in solvents of intermediate proton‐donor power like alcohols and methylformamide both IIa and IIb species coexist with comparable proportion (24). Pyridoxic acid does not undergo tautomerization (25). In this case, the lack of tautomerization is due to the stabilization of the phenolic oxygen by intramolecular hydrogen bonding with the carboxylic group.…”
Section: Resultsmentioning
confidence: 99%